SEMIOTIKA DALAM PUISI HUJAN BULAN JUNI KARYA SAPARDI DJOKO DAMONO - Deden Much. Darmadi (Universitas Sultan Ageng Tirtayasa, 2018)
Poetry is a tool to express the feeling, idea, and imagination in the form of written language. For understanding the meaning of a poetry is needed a research, this research will help someone to understand the meaning of poetry. There are many approach to understand the poetry. The approach is should be appropriate with the neoessityin understanding the poetry. The poetry which is entitled “Hujan Bulan Juni” by Sapardi Djoko Damono is undertood by using semiotic approach. Based on the semiotic approach, there same some icon and symbol in each row. By using heuristic approach, some in each sentences row. There are many meaning. Whereas by using hermeneutic approach, the poetry which is entitled “Hujan Bulan Juni”. As we know that June is dry season, so that poetry means waiting. It describessome one who wait for a beloved one.